POLITENESS IN ADELINEâ€™S IMPLICATURE IN â€œTHE AGE OF ADELINEâ€ MOVIE - NUR ANGGRAETA, JULIA (LANGUAGE HORIZON, 2016)
Abstrak Komunikasi koperatif merupakan syarat dari terbentuknya komukasi efektif. Perkataan seseorang dapat mempengaruhi jalannya komukasi yang berlangsung antara pembicara dan pendengar. Akan tetapi, tidak semua asas koperatif untuk berkomunikasi harus dilakukan. Melalui implikatur, pembicara dapat memberikan makna tambahan dalam perkataan mereka. Salah satu film yang menggunakan implikatur dalam percakapan adalah The Age of Adeline. Dalam film ini, Adeline menggunakan implikatur dalam perkataanya dengan tujuan untuk menyembunyikan identitasnya. Hal ini tidak mudah baginya karena dia harus terus menerus menyembunyikan identitas dari tahun ke tahun. Maka dari itu, Adeline menerapkan asas kesopanan dalam implikaturnya. Hal itu membantunya menjadikan identitasnya tetap aman dan agar orang-orang disekitarnya tidak merasa terancam olehnya. Adeline menerapkan empat dari enam asas kesopanan yang dirumuskan oleh Leech (1983), yaitu asas kebijaksanaan, kedermawanan, pujian, dan asas kesederhanaan. Penerapan asas-asas tersebut dipengaruhi oleh beberapa factor sosial, antara lain kelas sosial, hubungan sosial, dan fungsi dari percakapan antar lawan bicara. Kata kunci: koperatif, implikatur, kesopanan, factor sosial. Abstract Cooperative communications is a requirement of the establishment of an effective commucation. Someone’s utterances could affect the course of the communication that takes place between the speaker and the listener. However, not all the cooperative principle to communicate should be done. Through implicature, the speaker could give additional conveyed meaning in their utterances. One of the movies that apply implicature in the conversation is The Age of Adeline. In this movie, Adeline uses implicatures in her utterance in order to hide her identity. It is not easy for her because she must continue to hide the identity from year to year. Therefore, Adeline applies the politeness principles in her implicatur. It helped her turn her identity remain safe so people around her do not feel threatened by her. Adeline applies four of the six politeness principles formulated by Leech (1983); they are tact maxim, generosity maxim, approbation maxim, and modesty maxim. The application of these principles is influenced by several social factors, such as social class, social relationships, and functions of the conversation between the interlocutors. Keywords: cooperative, implicatures, politeness, social factors.